Environmental effect of ZOCO (Zro2/Ceo2) nano composite in methyl ester from canola oil through the performance and emission studies on IC engine. (2020) - Prathima, A.; Karthikeyan, S.; Mahalakshmi, S.; Thenappan, T.
Abstract: The aim of the present study is to analyze the effect of ZOCO (Zro2 /Ceo2 ) nano composite on engine performance and emissions characteristics of a diesel engine fuelled with Canola Methyl Ester (CME). The blend B20 (80% Petro diesel + 20% CME) and various ZOCO nano composite blended fuels such as B20ZOCO20 (B20 + 20 ppm-ZOCO), B20ZOCO40 (B20 + 40 ppm-ZOCO) B20ZOCO60 (B20 + 60 ppm-ZOCO) B20ZOCO80 (B20 + 80 ppm-ZOCO) were prepared. The ZOCO nano composite was mixed with B20 with the aid of a ultrasonicator. All the tests related to performance and emission characteristics were carried out. The test results show that addition of nano composite improves the Brake Thermal Efficiency (BTE) and reduces Brake specific fuel consumption (BSFC) at full load conditions and effective in control of carbon monoxide (CO) and oxides of nitrogen (NOx ). In this study, canola oil was transesterified with methanol using sodium hydroxide as a catalyst to obtain Canola Methyl Ester (CME) and characterized by Fourier Tranform Infrared (FT-IR) spectrum and Nano composites ZOCO were prepared by a microwave combustion method utilizing Cerium (III) nitrate hexa -hydrate, Zirconium (IV) Oxynitrate Hydrate and Urea as precursors and it was characterized by Scanning Electron Microscope (SEM).